2017
DOI: 10.1186/s13063-017-1912-9
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory oxygen in fibrotic lung disease (AmbOx): study protocol for a randomised controlled trial

Abstract: BackgroundFibrotic interstitial lung diseases (ILDs) are chronic and often progressive conditions resulting in substantial morbidity and mortality. Shortness of breath, a symptom often linked to oxygen desaturation on exertion, is tightly linked to worsening quality of life in these patients. Although ambulatory oxygen is used empirically in their treatment, there are no ILD-specific guidelines on its use. To our knowledge, no studies are available on the effects of ambulatory oxygen on day-to-day life in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…In a two period crossover, it is impossible to separate carryover (be it pharmacological or psychological) from treatment by period interaction (32). Given these uncertainties, we took the a priori decision to adjust for order of treatment (18), as this takes into account the possibility of a difference in effect according to treatment sequence. However, the unadjusted analysis of the primary outcome, where sequence is omitted, can be found in the supplementary file (supplementary table 4, p5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a two period crossover, it is impossible to separate carryover (be it pharmacological or psychological) from treatment by period interaction (32). Given these uncertainties, we took the a priori decision to adjust for order of treatment (18), as this takes into account the possibility of a difference in effect according to treatment sequence. However, the unadjusted analysis of the primary outcome, where sequence is omitted, can be found in the supplementary file (supplementary table 4, p5).…”
Section: Discussionmentioning
confidence: 99%
“…The AmbOx trial is a UK multi-centre, prospective, randomised, open label, mixed-method, controlled cross-over trial of portable ambulatory oxygen for two weeks, against no intervention for two weeks, to evaluate whether ambulatory oxygen is associated with improved HRQoL compared to no intervention in patients with fibrotic ILD. Approval of the final clinical protocol (18) was provided by the appropriate independent Ethics Committee (NRES Ref: 14/LO/0258).…”
Section: Methodsmentioning
confidence: 99%
“…A crossover trial comparing the efficacy of two portable oxygen concentrators with traditionally used compressed oxygen cylinders showed no significant differences in either the desaturation rate or 6‐min walk test (6MWT) distance . The complete results of the AmbOx study, a multicentre, prospective, randomized controlled crossover trial of ambulatory oxygen in patients with ILD, are eagerly anticipated (NCT02286063) …”
Section: Interstitial Lung Diseasementioning
confidence: 99%
“…A retrospective study of patients with different ILDs showed that home oxygen increased exercise tolerance and decreased dyspnea [8,9]. Recently, a clinical trial (the AmbOx study) has demonstrated that ambulatory oxygen could improve health-related quality of life [10] Moreover, given the multifactorial nature of the low exercise tolerance in patients with ILDs, the standard use of home supplemental oxygen therapy could not solve the whole problem. In COPD patients, multiple therapies have been described to solve this aspect.…”
Section: Introductionmentioning
confidence: 99%